Relational Space and Life Geographies in Imperial History: George Arthur and Humanitarian Governance - Lester, Alan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2010)
This paper focuses on the personality and agency of George Arthur, situating them within broader discursive assemblages. It begins by examining new approaches to the role of the individual in society that are linked to the relativisation of our ideas of space and place. It then examines three sets of relationships that shaped Arthur and, to varying extents, that he gained the capacity to shape: military networks, discourses of the family and humanitarian governance. Pointing to a specific combination of anti-democratic and humane notions of governance, it argues that Arthur’s acquisition of capacity in this sphere helped effect a transition from anti-slavery to humanitarian colonial governance in and across a variety of colonial spaces.